2005
DOI: 10.1007/s11745-005-1454-5
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for delivery of arachidonic acid to pacific oyster, Crassostrea gigas, spat

Abstract: The present study tested two techniques for dietary supplementation of Crassostrea gigas spat with PUFA, such as arachidonic acid (AA). The first technique consisted of a preliminary enrichment and growth of an algal concentrate (T-ISO, Isochrysis sp.) with AA dissolved in an ethanol solution, the whole culture then being fed to the spat. This enrichment increased the AA weight percentage in T-ISO neutral and polar lipids from 0.6 to 22.4% and from 0.4 to 6.8%, respectively. The second delivery technique was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…2006a). In addition, the fatty acid content of algae can be directly manipulated by adding fatty acid supplements to algal culture water (von Elert 2002; Seguineau et al. 2005).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2006a). In addition, the fatty acid content of algae can be directly manipulated by adding fatty acid supplements to algal culture water (von Elert 2002; Seguineau et al. 2005).…”
Section: Resultsmentioning
confidence: 99%
“…2005). Despite the ease with which this process is accomplished, the results of Seguineau et al. (2005) suggested that there might be biological changes to enriched algae that make it less suitable as food.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations